2022
DOI: 10.47391/jpma.aku-16
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of oncoplastic breast surgery in Pakistan

Abstract: Oncoplastic breast surgery is based on the concept of tumour-specific immediate reconstruction. It combines both local and distant techniques to maintain breast texture, symmetry and cosmesis without compromising oncological outcome. The current narrative review was planned to highlight the current state and future of oncoplastic breast surgery in low- and middle-incomecountries where its utilisation in surgical practice remains insubstantial because majority of the surgeons who are treating breast cancer are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…OPS is still in its early stages in Pakistan 28 and studies from Pakistan have shown that improved patient satisfaction and surgical outcomes. 13 , 29 , 30 With the advent of accredited breast surgery fellowship programs in Pakistan, it can be predicted that the growing interest in breast surgery research will allow for more meaningful and patient-oriented research in the field of OPS and hence, the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…OPS is still in its early stages in Pakistan 28 and studies from Pakistan have shown that improved patient satisfaction and surgical outcomes. 13 , 29 , 30 With the advent of accredited breast surgery fellowship programs in Pakistan, it can be predicted that the growing interest in breast surgery research will allow for more meaningful and patient-oriented research in the field of OPS and hence, the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 Alarmingly, statistics suggest one in nine Pakistani women will face this illness in their lifetime, making it the highest incidence rate in the region. 3 There's a heightened focus on the quality of life for patients undergoing surgery for breast malignancy with an added emphasis on improving the cosmetic outcome as a major objective for breast surgeons 4 . Although innovations in breast conservation surgery and advancement in oncoplastic procedures have gained popularity, mastectomy is still considered to be the preferred choice by patients and clinicians in developing countries.…”
Section: Introductionmentioning
confidence: 99%